Age, growth and stock assessment of the Indian mackerel Rastrelliger kanagurta (Cuvier, 1817) along the Sohar coast of Oman - Jayabalan, N.; Zaki, S.; Al-Kiyumi, F.; Al-Kharusi, L.; Al-Habsi, S. (Indian Journal of Fisheries, 2014)
A study on age, growth and stock characteristics of the Indian mackerel Rastrelliger kanagurta (Cuvier) was made from Sohar coast between 2007 and 2009. The length-weight relationship for the species can be expressed by the common formula, W = 0.0035TL 3.3881 . The growth parameters of R. kanagurta were L âˆž = 3 4.00 cm, K = 0.86 y -1 and t 0 = -0.06 y. The total mortality (Z) was 2.84 y -1 , the natural mortality rate (M) and fishing mortality (F) were 1.58 and 1.26 respectively. The exploitation rate (E) was less than 0.5. The estimates of MSY stood at 1512 t by Cadimaâ€™s formula. The predictive Thompson and Bell analysis indicated scope for marginal increase in Indian mackerel landings and the estimated MSY and corresponding F were 1,576 t and 1.4 respectively.